APLIKASI PENCARIAN LETAK GUDANG KOPERASI DENGAN METODE K-MEANS CLUSTER MENGGUNAKAN FRAMEWORK LARAVEL - Tristiyanto Tristiyanto; Bambang Hermanto; Afridho Rachmadi Kartawiria (Jurnal Pepadun, 2021)
Multi-cooperative information systems have been developed in 2018 by providing several services, one of which is GIS (geographic information system). GIS on this system displays the locations of existing cooperatives in the form of digital maps. This study develops the GIS service on a multi-cooperative information system into a cooperative warehouse location search using the K-means clustering method. Multi-cooperative information systems with cooperative warehouse location search features were developed using the Laravel 5.5 framework with the waterfall method. Searching the location of cooperative warehouses using the K-means method is useful to assist users in determining the location of warehouses to supply adjacent cooperatives. This system has also been tested using the Blackbox Testing method.